SIRI Learning Model in Empowering Biology Students' Critical Thinking - Asham Bin Jamaluddin; Muhiddin Palennari; Any Fatmawati; Evrialiani Rosba (Postgraduate, University of Mataram, 2023)
This research aims to investigate the influence of the SIRI learning model, namely learning based on integrated problem solving in Indonesian Siri' culture in improving the critical thinking skills of biology students. This experimental research was conducted with a pretest-posttest nonequivalent control group design and involved 109 biology students at Universitas Negeri Makassar, Universitas Pendidikan Mandalika, and Universitas PGRI Sumatera Barat, Indonesia. Data was collected using a critical thinking skills essay test. A critical thinking skills rubric was used to assess student answers and the results were analyzed using ANCOVA at a significance level of 0.05. Research findings show that there is an influence of the SIRI learning model on the critical thinking skills of biology students. The LSD test results show that the critical thinking skills of the SIRI class are significantly different from those of the PBL class and conventional class. It was concluded that the SIRI learning model could improve biology students' critical thinking skills.